POLA PEMBERIAN ASI DAN MAKANAN BAYI DI DESA SEMPULUR BOYOLALI - Iman Sumarno; Sri Prihatini; Basuki Budiman; Edwi Saraswati (Persagi, 1994)
POLA PEMBERIAN ASI DAN MAKANAN BAYI DI DESA SEMPULUR BOYOLALI